Analisis Hubungan Pendirian Objek Wisata Menara Pandang terhadap Peningkatan Jumlah Kunjungan Wisatawan ke Objek Wisata Salib Kasih - Dini Resavita Hariandja; Robert Juni Tua Sitio; Ade Putera Arif Panjaitan; Liyus Waruwu; Yulia K.S Sitepu (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
This study aims to analyze the relationship between the establishment of the Menara Pandang tourist attraction and the increase in the number of tourist visits to the Salib Kasih tourist destination. The research method used is qualitative with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation with several informants, namely the Technical Implementation Unit (UPT) of Salib Kasih and Menara Pandang, the Tourism Office of North Tapanuli, tourism workers, local business actors, and visiting tourists. The results of the study show that the establishment of Menara Pandang has a significant relationship with the increase in tourist visits to Salib Kasih. This relationship can be seen from the growth in the number of tourists coming after the development of the new facility, namely Menara Pandang. Supporting factors of this relationship include the proximity of the two tourist sites, the development of integrated tour packages, active promotion through social media, and support from the local government in providing facilities and infrastructure. With this integration, tourists who previously only visited Salib Kasih are now encouraged to also enjoy the attraction of Menara Pandang, thus extending their length of stay and giving a positive impact on the local economy. Furthermore, this study also found that the existence of Menara Pandang strengthens the image of Salib Kasih as a religious tourism destination as well as natural tourism with its unique features and attractions. Therefore, the development of additional strategic tourist attractions can be an effective step in increasing both attractiveness and the number of tourist visits, especially in religious and nature-based destinations. This research emphasizes the importance of collaboration among stakeholders in sustainable tourism development.